2021
DOI: 10.1002/acr.24179
|View full text |Cite
|
Sign up to set email alerts
|

Precision Medicine Approach to Develop and Internally Validate Optimal Exercise and Weight‐Loss Treatments for Overweight and Obese Adults With Knee Osteoarthritis: Data From a Single‐Center Randomized Trial

Abstract: This technical report provides additional statistical background for the methodology developed in the clinical analysis of knee osteoarthritis in Jiang et al. (2020). Jiang et al. (2020) proposed a pipeline to learn optimal treatment rules with precision medicine models and compared them with zero-order models with a Z-test. The model performance was based on value functions, a scalar that predicts the future reward of each decision rule. The jackknife (i.e., leave-one-out cross validation) method was applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 33 publications
(40 reference statements)
1
22
0
Order By: Relevance
“…The marked variations in disease expression and pathobiological manifestations in OA suggest the significant value of personalized and precision medicine from the therapeutic perspective 12,69,72 . Personalized medicine is used to treat patients on the basis of their individual clinical characteristics, taking account of the diversity of symptoms, severity, and genetic defects 73 . In precision medicine, molecular information maximizes the accuracy of patient classification and treatment, typically applying large amounts of data for the identification of patient phenotypes that share specific relevant characteristics to predict diagnosis, progression, or treatment response and utilize appropriate therapeutic targets 74,75 .…”
Section: Perspectivesmentioning
confidence: 99%
“…The marked variations in disease expression and pathobiological manifestations in OA suggest the significant value of personalized and precision medicine from the therapeutic perspective 12,69,72 . Personalized medicine is used to treat patients on the basis of their individual clinical characteristics, taking account of the diversity of symptoms, severity, and genetic defects 73 . In precision medicine, molecular information maximizes the accuracy of patient classification and treatment, typically applying large amounts of data for the identification of patient phenotypes that share specific relevant characteristics to predict diagnosis, progression, or treatment response and utilize appropriate therapeutic targets 74,75 .…”
Section: Perspectivesmentioning
confidence: 99%
“…Through proofs and simulations Jiang et al [7] showed consistency and asymptotic normality of the proposed jackknife estimator of the value function. Note that we are ignoring the contribution to the limiting distribution due to estimating the propensity scores.…”
Section: Methodsmentioning
confidence: 93%
“…The selected approach is then evaluated via cross-validation techniques for assessing the value function associated with the estimated treatment rule. Jiang et al [7] proposed a LOOCV or jackknife estimator for the value function for continuous outcomes. The approach requires weak assumptions, namely that the data are independent and identically distributed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations